Ethnopharmacological Analysis of Daun Mantangan (Decalabanthus Peltatus) Among the Indigenous Gemna Community in South Sorong - Franklin D. Paiki; Yustianto T.; Yudid Srywahyuni S.; James Aidore (Green Publisher Indonesia, 2025)
This study aims to examine the ethnopharmacological potential of Mantangan leaves (Decalabanthus peltatus), locally known as Glimit, among the Indigenous Gemna community in South Sorong Regency. The research employs a qualitative-descriptive approach within an interdisciplinary ethnopharmacological framework that integrates ethnographic findings and laboratory analyses. Data were collected through in-depth interviews, participant observation, and documentation of traditional healing practices, and further supported by phytochemical tests conducted at the Pharmacy Laboratory of STIKES Papua. The results reveal that Mantangan leaves have been traditionally used for generations to treat various ailments such as coughs, shortness of breath, asthma, eye irritation, wounds, and postpartum recovery. Phytochemical analysis identified the presence of flavonoids, saponins, tannins, and alkaloids with biological activities including anti-inflammatory, antimicrobial, and wound-healing properties. The synergy between traditional knowledge and scientific validation demonstrates that the Gemna community’s healing practices have a strong scientific basis and hold potential for development as a locally based herbal medicine from Papua.